Researches on social infrastructure development, in South Muntenia development region - Daniela Creţu; Radu Andrei Iova; Elena Lascăr (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The infrastructure constitutes a support element, with particular importance for supporting all economic and socio- cultural activities. The infrastructure covers both structural field, giving unity to the system unit and the spatial field, thus achieving a viable or not territorial configuration , which is reflected by different levels of accessibility in the physical, technical, economic or socio-cultural area. An important aspect for the development of the region, including the rural area, is the social infrastructure with reference to houses, education and health system. In this respect, in the present paper we propose the analysis of the social infrastructure, namely, house building, education and the health infrastructure, using as research methods, documenting, analyzing and processing the secondary analysis. The ascending dynamics of new house building in the rural area, can be combined with the dynamics of the population mobility and increasing economic importance of agricultural activities at social levels. The infrastructure for education is well represented in the region and thus it can support the development in good conditions of the educational act. From the analysed data, it results a deficiency of providing health infrastructure in the rural area, this situation requiring major investments made with projects funded under various development programs.
Keywords: 330; regional development; social infrastructure; houses fund; development potential